Effect of Aloe vera Hydrogel Application on Increasing the Number of Fibroblasts in Socket Wounds Post-Tooth Extraction: An In Vivo Study - Silvi Tiara Dewi; Chandra Susanto (HM Publisher, 2022)
Background. Aloe vera has been used as an anti-inflammatory, antimicrobial, and immune-boosting agent since ancient time. Hydrogel is a polymeric material that can retain a significant amount of water component and can last as long as possible in the gingival sulcus because the hydrogel is hydrophilic. This study is the first study that seeks to explore the potential of Aloe vera in healing socket wounds after tooth extraction. Methods. Twenty-five white rats of the Wistar strain were acclimatized for seven days before being included in the study. After acclimatization, the experimental animals were grouped into five groups. Evaluation of fibroblast response process with HE staining. Results. There were differences in the mean number of fibroblasts in all groups. From the results of this study, it can be stated that there is an effect of the application of hydrogel Aloe vera 1%, 2.5%, 5%, 10%, and xylazine on the increase in the number of fibroblasts in socket wounds after tooth extraction in Rattus novergicus. Conclusion. There is an effect of Aloe vera hydrogel application on increasing the number of fibroblasts in socket wounds after tooth extraction in Rattus novergicus.